1% Versus 2% Lignocaine for Airway Anesthesia in Flexible Bronchoscopy Without Lignocaine Nebulization (LIFE): A Randomized Controlled Trial. Issue 2 (April 2018) - Madan, Karan; Biswal, Shiba K.; Mittal, Saurabh; Hadda, Vijay; Mohan, Anant; Khilnani, Gopi C.; Pandey, Ravindra M.; Guleria, Randeep
Abstract : Background: The ideal concentration of lignocaine for topical anesthesia in bronchoscopy remains investigational. In this randomized, double blind study, we compared 1% versus 2% lignocaine for topical anesthesia. Methods: Consecutive patients undergoing bronchoscopy were randomized to receive either 1% or 2% lignocaine solution by spray-as-you-go technique. All received 10% lignocaine spray to the oropharynx along with nasal 2% lignocaine gel. Nebulized lignocaine was not administered. Primary outcomes were operator-rated overall procedural satisfaction, visual analogue scale (VAS)-rated and operator-rated cough, VAS. Secondary objectives were total lignocaine dose administered, patient-rated pain on faces pain scale, cumulative dose of lignocaine and procedural complications. Results: A total of 500 patients (250 in each group) were randomized. Baseline characteristics were comparable. Operator-rated overall procedural satisfaction, VAS (72.05±20.16 and 72.20±21.96 in 1% and 2% group respectively; P =0.93) and operator-rated cough, VAS [1% group: 19.1 (12.6-34.6) and 2% group: 20.6 (12.5-36.9); P >0.05] were similar between the 2 groups. Cumulative dose of lignocaine used in 2% lignocaine group was greater (220.89±12.96 mg in 1% and 319.55±19.32 mg in 2% group; P <0.001). Patients receiving sedation were comparable between the 2 groups. (10% in 1% lignocaine group and 6% in 2% lignocaine group; P =0.13). Minor complications occurred in 2 patients in each group. Conclusion: One percent lignocaine in flexible bronchoscopy is as efficacious as 2% lignocaine when administered using the spray as you go technique without concurrent lignocaine nebulization, at a significantly lower total dose of lignocaine administered.